2022
DOI: 10.5194/bg-19-201-2022
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriohopanetetrol-<i>x</i>: constraining its application as a lipid biomarker for marine anammox using the water column oxygen gradient of the Benguela upwelling system

Abstract: Abstract. Interpreting lipid biomarkers in the sediment archive requires a good understanding of their application and limitations in modern systems. Recently it was discovered that marine bacteria performing anaerobic ammonium oxidation (anammox), belonging to the genus Ca. Scalindua, uniquely synthesize a stereoisomer of bacteriohopanetetrol (“BHT-x”). The ratio of BHT-x over total bacteriohopanetetrol (BHT, ubiquitously synthesized by diverse bacteria) has been suggested as a proxy for water column anoxia. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…Notably, stereoisomers of BHT were not observed in any of the samples, despite 'late-eluting BHT isomers' being associated with modern marine water column suboxia/anoxia, as well as bacterial anaerobic oxidation of ammonium (anammox) activity (Sáenz et al, 2011;Wakeham et al, 2012;Kharbush et al, 2013;Rush et al, 2014;Matys et al, 2017Matys et al, , 2019Schwartz-Narbonne et al, 2020;van Kemenade et al, 2022). The lack of BHT isomer(s) supports previous studies which suggest that the isomerization of BHT and ratios of BHT to its isomer(s) are more indicative of anammox activity rather than simply suboxia/anoxia.…”
Section: Water Column Bhp Distributionmentioning
confidence: 98%
See 1 more Smart Citation
“…Notably, stereoisomers of BHT were not observed in any of the samples, despite 'late-eluting BHT isomers' being associated with modern marine water column suboxia/anoxia, as well as bacterial anaerobic oxidation of ammonium (anammox) activity (Sáenz et al, 2011;Wakeham et al, 2012;Kharbush et al, 2013;Rush et al, 2014;Matys et al, 2017Matys et al, , 2019Schwartz-Narbonne et al, 2020;van Kemenade et al, 2022). The lack of BHT isomer(s) supports previous studies which suggest that the isomerization of BHT and ratios of BHT to its isomer(s) are more indicative of anammox activity rather than simply suboxia/anoxia.…”
Section: Water Column Bhp Distributionmentioning
confidence: 98%
“…Additionally, it has been suggested that the ratio of bacteriohopanetetrol (BHT) to its isomer(s) in sediments can be used as a proxy for suboxicanoxic water column conditions (Sáenz et al, 2011). The presence of specific BHT isomers has more recently been associated with anaerobic ammonium-oxidation (anammox), an important microbial process in the nitrogen cycle (e.g., Rush et al, 2014;Matys et al, 2017;Schwartz-Narbonne et al, 2020;van Kemenade et al, 2022). Many studies now postulate that C-2 methylated hopanoids (originally thought to be indicative of oxygenic photosynthesis; Summons et al, 1999) are produced in response to myriad environmental stressors (e.g., changes in pH, redox, nutrient availability, solar irradiance), combinations of which are still being revealed (see review by Newman et al, 2016 and references therein;Matys et al, 2019a).…”
Section: Introductionmentioning
confidence: 99%
“…Babbin et al (2014) showed, using incubations from the ETNP OMZ, that anammox rates increase in response to the addition of OM. Likewise, in the modern Southern Pacific OMZ, N loss by anammox was found to be strongly correlated with the export of OM, via the release of ammonium into the water column through remineralization (Kalvelage et al, 2013). As such, the co-occurrence of ladderane FA and paleoproductivity proxy maxima during MIS 5 could reflect an increase in Ca.…”
Section: The Holocene and Mis 5 Including The Penultimate Interglacia...mentioning
confidence: 91%
“…modern annual aver- age bottom water temperatures at Site 1012 are < 5 °C; Garcia et al, 2019). Additionally, while the transport of ladderane FAs has been shown to occur within oxygen-depleted systems (van Kemenade et al, 2022), long-distance transport of ladderane FAs with the CU (characteristic DO concentration of ∼ 62 µmol L −1 in modern CU water; Sahu et al, 2022) is unlikely, and it would be expected to yield higher relative abundances of SC-ladderane FAs than detected in the record. Transport of ladderanes is also not reflected in present-day ENP ladderane distributions, as an investigation of ladderanes at more northerly (∼ 20°N) and more southerly (∼ 17°N) located sites showed in situ synthesis by pelagic Ca.…”
Section: Ladderanes Sourced From Anammox Bacteria In the Estnp Omz Wa...mentioning
confidence: 99%
See 1 more Smart Citation